Intelectualidade, identidade e progresso no Mato Grosso: a história da historiografia de Virgílio Corrêa Filho (1922-1969) - Rozendo, Lucas Queiroz (2024)
The dissertation investigates the historiographical production of Virgílio Corrêa Filho (1887- 1973), exploring his trajectory linked to the main intellectual production institutions of the 20th century. The study conducts an analysis of the Mato Grosso identity construction by Corrêa Filho in the 1920s and 1940s. Furthermore, it examines his representation of nature, as a defender of the occupation and exploitation of Mato Grosso territories, in order to integrate the region into the modernization process of the State and Brazilian society. The study seeks to understand the formation of an intellectual project based on the search for a local identity, grounded on the notions of progress and modernization of Mato Grosso, as the central pillars of the historiographical thought of Virgílio Corrêa Filho proposed here